KEBERADAAN HUKUM UU OMNIBUS LAW DALAM SISTEM HUKUM INDONESIA - Soimin, Soimin (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2021)
To initiate the discussion about what is meant by the Omnibus Law, which later became controversial over the government's choice to propose a draft Law on Job Creation submitted to the House of Representatives (DPR), when the draft Omnibus Law draft was still being debated from side of the legal position in the Indonesian legal system. Apart from the debate regarding the policies of the Joko Widodo - KH. Ma`ruf Amin government regarding the Omnibus Law, we need to explore the use and utilization of omnibus law policies in the applicable legal system and the State that uses this concept. Given, the concept of omnibus law in practice is often used by countries that adhere to the â€œcommon lawâ€ legal system, not countries that adhere to the â€œcivil lawâ€ legal system. And how the Indonesian State, which adopts the civil law legal system, applies the concept of the omnibus law policy in its legal system. ABSTRAKSI Untuk mengawali pembahasan tentang apa yang dimaksud dengan Undang-Undang (UU) Omnibus Law, yang kemudian menjadi kontroversial atas pilihan pemerintah untuk mengusulkan rancangan UU tentang Cipta Kerja yang diajukan kepada Dewan Perwakilan Rakyat (DPR), ketika draft rancangan UU Omnibus Law masih diperdebatkan dari sisi kedudukan hukum di dalam sistem hukum Indonesia. Terlepas dari perdebatan mengenai kebijakan pemerintahan Joko Widodo â€“ KH. Ma`ruf Amin mengenai UU Omnibus Law perlu kita telusuri penggunaan dan pemanfaatan kebijakan omnibus law di dalam sistem hukum yang berlaku dan Negara yang menggunakan konsep tersebut. Mengingat, konsep omnibus law di dalam praktek pada dasarnya, sering digunakan oleh Negara yang menganut sistem hukum â€œcommon lawâ€, bukan Negara yang menganut sistem hukum â€civil lawâ€. Dan bagaimana Negara Indonesia yang menganut sistem hukum civil law mempraktekkan kebijakan konsep omnibus law di dalam sistem hukumnya.